2019
DOI: 10.1590/0100-29452019120
|View full text |Cite
|
Sign up to set email alerts
|

Torsion of canes and hydrogenated cyanamide in bud bursting and production of grapevine cv. Itália muscat in the São Francisco valley

Abstract: The grapevine cultivated in tropical regions, such as the Sub-medium of the São Francisco Valley, exhibits a strong bud dormancy and high apical dominance, thus presenting the need for the utilization of products that promote the dormancy breaking of the buds. The aim of the present work was to evaluate the efficiency of the application of hydrogenated cyanamide and the practice of cane torsion over the breaking of bud dormancy, bud burst and yield of grapevine cv. Italia Muscat in the conditions of the Sub-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…There are numerous substances, including thiourea, potassium nitrate, ethephon, paclobutrazol, and calcium cyanamide, have been used to encourage the breaking of buds in tropical grapevines. However, it has been found that Hydrogen Cyanamide (H2CN2) is the most effective, encouraging favorable effects in the plant's productive features, particularly in the flowering percentage, and, as a result, in the crop yields [12]. In table grapes a lack of winter chilling might cause unequal bud bursting, prolonged flowering, and delayed fruit development.…”
Section: Why Uniform Bud Break Is Neededmentioning
confidence: 99%
“…There are numerous substances, including thiourea, potassium nitrate, ethephon, paclobutrazol, and calcium cyanamide, have been used to encourage the breaking of buds in tropical grapevines. However, it has been found that Hydrogen Cyanamide (H2CN2) is the most effective, encouraging favorable effects in the plant's productive features, particularly in the flowering percentage, and, as a result, in the crop yields [12]. In table grapes a lack of winter chilling might cause unequal bud bursting, prolonged flowering, and delayed fruit development.…”
Section: Why Uniform Bud Break Is Neededmentioning
confidence: 99%